(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Praptiwi Windadri FI, Sulistiarini D, Ersaliany NPQ. 2022. Potential bioactivity evaluation of Arytera littoralis Blume (Sapindaceae). Biodiversitas 23: 4977-4983. Bioactivity of Arytera littoralis (Sapindaceae) and its chemical compounds from different parts of the plants (flower, leaves, and stem) using the different polarities of solvents was carried out in this study. Phytochemical analysis was performed using the standard method. Total phenolic content (TPC) and total flavonoid contents (TFC) were analyzed using spectrophotometry method. Out a qualitative assay for antioxidant and antibacterial activity against Streptococcus aureus and Escherichia coli was carried out by Bioautography-Thin Layer Chromatography (TLC). The minimum inhibitory concentration (MIC) value and IC50 value for antioxidant was carried out by microdilution methods on a 96-well microtiter plate. The results showed that different parts of the plant contained different phytochemical compounds. The highest TPC and TFC were obtained from stem extract, followed by leaves and flowers. The antibacterial activity of A. littoralis extracts against S. aureus and E. coli was categorized as weak antibacterial, while their antioxidant activity was categorized as a strong antioxidant. The antioxidant activity index (AAI) has a very strong correlation with TPC, TFC, and IC50 value.